Prognostic durability of coronary computed tomography angiography. (28th October 2020) - Chow, Benjamin J W; Yam, Yeung; Small, Gary; Wells, George A; Crean, Andrew M; Ruddy, Terrence D; Hossain, Alomgir
Abstract: Aims : This large prospective cohort study sought to confirm the incremental prognostic value of coronary computed tomographic angiography (CCTA) measured over a prolonged follow-up duration. CCTA has diagnostic and prognostic value but data supporting its long-term prognostic value in a large prospectively recruited cohort with suspected coronary artery disease (CAD) has been limited. Methods and results : Consecutive patients (without history of myocardial infarction, revascularization, cardiac transplantation, and congenital heart disease) were prospectively enrolled. CCTA was evaluated for CAD severity, total plaque score (TPS), and left ventricular ejection fraction. Patients were followed for major adverse events (MAE) and major adverse cardiac events (MACE). Over a total of 99 months, 8667 consecutive CCTA patients (mean age = 57.1 ± 11.1 years, 52.9% men) were prospectively enrolled and followed for a mean duration of 7.0 ± 2.6 years. At follow-up, there were a total of 723 MAE, 278 MACE, 547 all-cause deaths, 110 cardiac deaths, and 104 non-fatal myocardial infarction. Patients without coronary atherosclerosis at the time of CCTA had a very low annual event rate for both MAE and MACE (0.45%/year and 0.19%/year, respectively). Both MAE and MACE increased with increasing TPS and severity of CAD. In patients with non-obstructive CAD and who were statin-naive, TPS ≥5 had MACE rates >0.75%/year. Patients with high-risk CAD had an annual MAE and MACE rates of 3.52%/year and 2.58%/year, respectively. Adjusted hazard ratio of the severity of CAD based on multivariable analyses indicated that the prognostic values were incremental. Conclusion : CCTA has independent and incremental prognostic value that is durable over time. The absence of coronary atherosclerosis portends an excellent prognosis. Patients with increasing non-obstructive plaque burden have worse prognosis and a TPS threshold ≥5 may identify a population that may benefit from statin therapy.